ANALISIS PELAYANAN SAMSAT DELIVERY DALAM MENINGKATKAN LAYANAN PUBLIK DI BAPPENDA NTB (SAMSAT TALIWANG) - AGUSTHANAYA AGUSTHANAYA; UMAR UMAR; RODIANTO RODIANTO (Universitas Mahasaraswati K. Mataram, 2024)
Public demands for improved services in terms of vehicle equipment and easy and fast administration, due to the increasing mobility of people in traffic. the problem of service times coinciding with people's working hours. Often people have to abandon their activities. If the services provided are not on time, people have to spend more time processing their motor vehicle taxes. The method used in this research is qualitative method. Qualitative research is research into a process, event or development where the materials or data collected are in the form of qualitative information and the results of the research are not to be used as generalizations like quantitative research.The results of this research are based on observations of the availability of facilities provided by the Taliwang Samsat, service facilities are in good condition. The payment and delivery process for the Samsat delivery service is also carried out and carried out well. The inhibiting factors for the Samsat delivery application are 1) poor internet connectivity, 2) payment process and sending proof of PKB, 3) changes in regulations and online services, 4) lack of training regarding the application and 5) excessive and complicated bureaucracy.The conclusion of this research is; The Samsat Delivery application is very useful for the community and government in terms of Samsat motorized vehicles. Good internet connectivity, the process of using the Samsat delivery application will be of maximum benefit, as well as implementing efficient government administration. Samsat Taliwang has a positive innovation that helps people take care of vehicle taxes without having to physically visit the Samsat office by using Samsat Delivery technology